fLyapext

The function X_\mathrm{e}=fLyapext(X,Y,type) constructs the extended Lyapunov matrix X_\mathrm{e} in various fashions. Given the symmetric and nonsignular matrices X and Y (perturb if necessary), the function can be extended the Lyapunov function X_e such that:

TypesDescription
1-6For the coupling condition

\left(\begin{array}{cc}Y&I\\I&X\end{array}\right)\succ0

construct the extended Lyapunov matrix X_\mathrm{e} such that

X_\mathrm{e}^{-1}=\left(\begin{array}{cc}X&\star\\ \star&\star\end{array}\right)^{-1}=\left(\begin{array}{cc}Y&\star\\ \star&\star\end{array}\right)
7-12For the coupling condition

\left(\begin{array}{cc}Y&I\\I&X\end{array}\right)\succ0

construct the extended Lyapunov matrix X_\mathrm{e} such that

X_\mathrm{e}^{-1}=\left(\begin{array}{cc}X&\star\\ \star&\star\end{array}\right)^{-1}=\left(\begin{array}{cc}Y^{-1}&\star\\ \star&\star\end{array}\right)
13-15For the coupling condition

\left(\begin{array}{ccc}Y_{11}+X_{11}&Y_{12}&-X_{12}\\ Y_{12}^T&Y_{22}&I\\-X_{12}^T&I&X_{22}\end{array}\right)\succ0

with

X=\left(\!\!\begin{array}{cc}X_{11}&X_{12}\\ X_{12}^T&X_{22}\end{array}\!\!\right),\ Y=\left(\!\!\begin{array}{cc}Y_{11}&Y_{12}\\ Y_{12}^T&Y_{22}\end{array}\!\!\right)

construct the extended Lyapunov matrix X_\mathrm{e} such that

X_\mathrm{e}^{-1}=\left(\begin{array}{cc}X&\star\\ \star&\star\end{array}\right)^{-1}=\left(\begin{array}{cc}Y&\star\\ \star&\star\end{array}\right)

The different types are constructed as follows

TypeDescription
1

    \[X_\mathrm{e}=\left(\begin{array}{cc}X&I\\I&(X-Y^{-1})^{-1}\end{array}\right)\]

2

    \[X_\mathrm{e}=\left(\begin{array}{cc}X& X-Y^{-1} \\ X-Y^{-1} &X-Y^{-1}\end{array}\right)\]

3If Y\succ0, let Y=Y_\mathrm{c}^TY_\mathrm{c} (by means of a Cholexki factorization) and let Y_\mathrm{ci}= Y_\mathrm{c}^{-1}. Then

    \[X_\mathrm{e}=\left(\begin{array}{cc}X& X Y_\mathrm{c}^T- Y_\mathrm{ci}\\  Y_\mathrm{c}X- Y_\mathrm{ci}^T & Y_\mathrm{c}XY_\mathrm{c}^T -I\end{array}\right)\]


If Y is indefinite, let Y=M^TJM with J=\mathrm{diag}(I,-I) and M_\mathrm{i}=M^{-1}. Then

    \[X_\mathrm{e}=\left(\begin{array}{cc}X& X M^T- M_\mathrm{i}J\\  MX- JM_\mathrm{i}^T & MXM^T -J\end{array}\right)\]

4

    \[X_\mathrm{e}=\left(\begin{array}{cc}X& XY-I \\ YX-I &YXY-Y\end{array}\right)\]

5If X and Y are positive definite, let X=M^TM and Y=N^TN (by means of a Choleski factorization) and let M_\mathrm{i}=M^{-1}, N_\mathrm{i}=N^{-1}, and U\Sigma V^T=N_\mathrm{i}^TM_\mathrm{i}-NM^T. Then

X_\mathrm{e}=\left(\begin{array}{cc}M_\mathrm{i}^T&0\\N&U\Sigma^{\frac{1}{2}}\end{array}\right)^{-1} \left(\begin{array}{cc}M&V\Sigma^{\frac{1}{2}}\\N_\mathrm{i}^T&0\end{array}\right)

If X or Y is indefinite, let X=M^TJ_xM and Y=N^TJ_yN with J_x=\mathrm{diag}(I,-I) and J_y=\mathrm{diag}(I,-I). Also let M_\mathrm{i}=M^{-1}, N_\mathrm{i}=N^{-1} and U\Sigma V^T=N_\mathrm{i}^TM_\mathrm{i}-J_yNM^TJ_x. Then
X_\mathrm{e}=\left(\begin{array}{cc}M_\mathrm{i}^T&0\\J_yN&U\Sigma^{\frac{1}{2}}\end{array}\right)^{-1} \left(\begin{array}{cc}J_xM&V\Sigma^{\frac{1}{2}}\\N_\mathrm{i}^T&0\end{array}\right)
6If X\succ0, let X=X_\mathrm{c}^TX_\mathrm{c} (by means of a Cholexki factorization) and let X_\mathrm{ci}= X_\mathrm{c}^{-1}. Then

    \[X_\mathrm{e}=\left(\begin{array}{cc}X& X_\mathrm{c}^T- Y^{-1}X_\mathrm{ci}\\  X_\mathrm{c}-X_\mathrm{ci}^TY^{-1} &I-X_\mathrm{ci}^TY^{-1}X_\mathrm{ci}\end{array}\right)\]


If X is indefinite, let X=M^TJM with J=\mathrm{diag}(I,-I) and M_\mathrm{i}=M^{-1}. Then

    \[X_\mathrm{e}=\left(\begin{array}{cc}X&M^TJ-Y^{-1}M_\mathrm{i}\\JM- M_\mathrm{i}^TY^{-1} & J-M_\mathrm{i}^TY^{-1}M_\mathrm{i}\end{array}\right)\]

7

    \[X_\mathrm{e}=\left(\begin{array}{cc}X&I\\I&(X-Y)^{-1}\end{array}\right)\]

8

    \[X_\mathrm{e}=\left(\begin{array}{cc}X& X-Y \\ X-Y&X-Y\end{array}\right)\]

9If Y\succ0, let Y=Y_\mathrm{c}^TY_\mathrm{c} (by means of a Cholexki factorization) and let Y_\mathrm{ci}= Y_\mathrm{c}^{-1}. Then

    \[X_\mathrm{e}=\left(\begin{array}{cc}X& XY_\mathrm{ci}-Y_\mathrm{c}^T\\  Y_\mathrm{ci}^TX-Y_\mathrm{c}&Y_\mathrm{ci}^TXY_\mathrm{ci} -I\end{array}\right)\]


If Y is indefinite, let Y=M^TJM with J=\mathrm{diag}(I,-I) and M_\mathrm{i}=M^{-1}. Then

    \[X_\mathrm{e}=\left(\begin{array}{cc}X& XM_\mathrm{i}-M^TJ\\ M _\mathrm{i}^TX-JM& M_\mathrm{i}^TXM_\mathrm{i}-J\end{array}\right)\]

10

    \[X_\mathrm{e}=\left(\begin{array}{cc}X&XY^{-1}-I \\Y^{-1} X-I &Y^{-1}XY^{-1} -Y^{-1} \end{array}\right)\]

11If X and Y are positive definite, let X=M^TM and Y=N^TN (by means of a Choleski factorization) and let M_\mathrm{i}=M^{-1}, N_\mathrm{i}=N^{-1}, and U\Sigma V^T=N^TM_\mathrm{i}-N_\mathrm{i}^TM^T. Then

X_\mathrm{e}=\left(\begin{array}{cc}M_\mathrm{i}^T&0\\N_\mathrm{i}^T&U\Sigma^{\frac{1}{2}}\end{array}\right)^{-1} \left(\begin{array}{cc}M&V\Sigma^{\frac{1}{2}}\\N&0\end{array}\right)

If X or Y is indefinite, let X=M^TJ_xM and Y=N^TJ_yN with J_x=\mathrm{diag}(I,-I) and J_y=\mathrm{diag}(I,-I). Also let M_\mathrm{i}=M^{-1}, N_\mathrm{i}=N^{-1} and U\Sigma V^T=NM_\mathrm{i}-J_yN_\mathrm{i}^TM^TJ_x. Then
X_\mathrm{e}=\left(\begin{array}{cc}M_\mathrm{i}^T&0\\J_yN_\mathrm{i}^T&U\Sigma^{\frac{1}{2}}\end{array}\right)^{-1} \left(\begin{array}{cc}J_xM&V\Sigma^{\frac{1}{2}}\\N&0\end{array}\right)
12If X\succ0, let X=X_\mathrm{c}^TX_\mathrm{c} (by means of a Cholexki factorization) and let X_\mathrm{ci}= X_\mathrm{c}^{-1}. Then

    \[X_\mathrm{e}=\left(\begin{array}{cc}X&X_\mathrm{c}^T- YX_\mathrm{ci}\\  X_\mathrm{c}-X_\mathrm{ci}^TY&I-X_\mathrm{ci}^TYX_\mathrm{ci}\end{array}\right)\]


If X is indefinite, let X=M^TJM with J=\mathrm{diag}(I,-I) and M_\mathrm{i}=M^{-1}. Then

    \[X_\mathrm{e}=\left(\begin{array}{cc}X&M^TJ-YM_\mathrm{i}\\JM- M_\mathrm{i}^TY&J-M_\mathrm{i}^TYM_\mathrm{i}\end{array}\right)\]

13

    \[X_\mathrm{e}=\left(\begin{array}{ccc}X_{11}&X_{12}&X_{13}\\  X_{12}^T&X_{22}&X_{23}\\ X_{13}^T&X_{23}^T&X_{33} \end{array}\right)\]

where
X_{13}=\left(\begin{array}{cc}M_{12}&I\end{array}\right), X_{23}=\left(\begin{array}{cc}M_{22}&0\end{array}\right), X_{33}=\left(\begin{array}{cc}M_{22}&0\\0&M_{33}\end{array}\right), M_{12}=X_{12}+Y_{12}Y_{22}^{-1}, M_{22}=X_{22}-Y_{22}^{-1}, M_{3}=X_{11}+Y_{11}-Y_{12}Y_{22}^{-1}Y_{12}^T-M_{12}M_{22}^{-1}M_{12}^T
14

    \[X_\mathrm{e}=\left(\begin{array}{ccc}X_{11}&X_{12}&X_{13}\\  X_{12}^T&X_{22}&X_{23}\\ X_{13}^T&X_{23}^T&X_{33} \end{array}\right)\]

where
X_{13}=\left(\begin{array}{cc}A&C\end{array}\right), X_{23}=\left(\begin{array}{cc}B&A^T\end{array}\right), X_{33}=\left(\begin{array}{cc}B&A^T\\A&C\end{array}\right), A=X_{12}+Y_{12}Y_{22}^{-1}, B=X_{22}-Y_{22}^{-1}, C=X_{11}+Y_{11}-Y_{12}Y_{22}^{-1}Y_{12}^T
15

    \[X_\mathrm{e}=\left(\begin{array}{ccc}X_{11}&X_{12}&X_{13}\\  X_{12}^T&X_{22}&X_{23}\\ X_{13}^T&X_{23}^T&X_{33} \end{array}\right)\]

where
X_{13}=\left(\begin{array}{cc}A&B\end{array}\right), X_{23}=\left(\begin{array}{cc}C&D\end{array}\right), X_{33}=\left(\begin{array}{cc}E&F\\F^T&G\end{array}\right), A=X_{12}Y_{22}+Y_{12}, B=Y_{11}+X_{12}Y_{12}^T, C=X_{22}Y_{22}-I, D=X_{22}Y_{12}^T, E=Y_{22}X_{22}Y_{22}-Y_{22}, F=C^TY_{12}^T, G=Y_{12}X_{22}Y_{12}^T-Y_{11}

Previous page